Point Sampling Trial in a Sal (Shorea robusta) Forest - Negi, G. S.; Rawat, D. S. (Indian Forester, 1971)
The paper presents the estimates of Basal Area from point sampling with prisms of BAF-l, 2, 3, 4 and 5 sq m/hectare and compares them with those from plot sampling with 0.16 hectare plots in a pure sal forest. No significant difference in the estimates of basal area were observed either between the estimates from various prisms or between the two methods of sampling. The relative efficiency of point sampling taking time of cruise into consideration worked out from 200% to 400%, although the estimates from plot sampling were more precise. Prism of Basal Area Factor of 3 sq m/hectare is recommended for similar crops. It has been suggested that to estimate volume with a margin of error of 10% with a prism of BAF-3, about 50 sample points may be needed. However, the same accuracy could also be achieved even if measurements for volume are taken at comparatively lesser number of sample points and basal area which requires less time, estimated from a larger number of sample points.